Role of central nitric oxide in behavioral thermoregulation of toads during hypoxia - Guerra, Aline R. G. [UNESP]; Gargaglioni, Luciane H. [UNESP]; Noronha-De-Souza, Carolina R.; Abe, Augusto Shinya [UNESP]; Branco, Luiz G. S.; Bicego, Kenia C. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Nitric oxide (NO) is thought to play a key role in the development of hypoxia-induced anapyrexia in mammals, acting on the preoptic region of the anterior hypothalamus to activate autonomic heat loss responses. Regarding behavioral thermoregulation, no data exists for NO modulation/mediation of thermoregulatory behavior changes during hypoxia. Therefore, we tested the hypothesis that NO is involved in the preferred body temperature (Tb) reduction in the hypoxic toad Chaunus schneideri (formerly Bufo paracnemis), a primarily behavioral thermoregulator. Toads equipped with a temperature probe were placed in a thermal gradient chamber, and preferred Tb was monitored continuously. We analyzed the effect of intracerebroventricular injections of the nonselective NO synthase inhibitor L-NMMA (200, 400 and 800 microg per animal) or mock cerebrospinal fluid (mCSF, vehicle) on the preferred Tb of toads. No significant difference in preferred Tb was observed after L-NMMA treatments. Another group of toads treated with 2 mg kg(-1) (400 microg per animal) of L-NMMA or mCSF was submitted to hypoxia (3% inspired 02) for 8 h. The vehicle group showed a reduction of preferred Tb, a response that was inhibited by L-NMMA. A 3rd group of hypoxic animals was injected with Ringer or L-NMMA (2 mg kg(-1)) into the lymph sac and both treatments induced no change in the anapyretic response to hypoxia. These results indicate that NO acting on the central nervous system has an excitatory role for the development of hypoxia-induced anapyrexia in toads. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: preferred body temperature; L-NMMA; thermal gradient; Bufo; Chaunus; nitric oxide synthase